Halal Food, Religiosity, and Attitudes Toward Intention to Use Products and Services of Sharia-Compliant Hotels in Lombok, West Nusa Tenggara - Rusmiati, Rosida (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study was motivated by the limited research on tourist behavior towards Sharia-compliant hotels. Lombok Island was selected for this study due to its recognition as the premier halal tourism destination in Indonesia, showcasing significant advancements and attractions that cater to the needs of Muslim travelers. Its objective is to predict how halal food, religiosity, and the attitudes of Muslim tourists influence their intention to utilize products and services offered by Sharia-compliant hotels. Structural equation modeling was employed with a sample of 154 visitors to Sharia-compliant hotels on Lombok Island, namely Grand Legi Hotel, Lombok Plaza Hotel, Lombok Raya Hotel, Pratama Hotel, and Santika Hotel. The findings reveal that both halal food and religiosity exert positive influences on attitudes, subsequently enhancing the intention of Muslim tourists to use the products and services provided by Sharia-compliant hotels. We recommend that future research explore other variables influencing tourists' attitudes and intentions to use Sharia-compliant hotel products and services. Additionally, tourism policymakers should pay attention to the importance of halal food and beverages and the religiosity of tourists to enhance the overall quality of halal tourism.